[Afisz. Incipit] Program uroczystości środa, dnia 21.VII. b.r. ... (Sopot : [wydawca nieznany], 1948)
Afisz informujący o Akademii wraz z programem.
Keywords: Grand Hotel (Sopot, Polska, budynek) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.